If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8-2x=3x+33
We move all terms to the left:
8-2x-(3x+33)=0
We get rid of parentheses
-2x-3x-33+8=0
We add all the numbers together, and all the variables
-5x-25=0
We move all terms containing x to the left, all other terms to the right
-5x=25
x=25/-5
x=-5
| 8–2x=3x+33 | | 5x+3=3x+11 | | 4/5x-1/2+5/2x=2+3/2x-1/4 | | -z+3/2=-2 | | 3+3y=1-3y | | 10/3x+(1/2)=4/3 | | 6=-q/4+7 | | 10/3x+1/2=4/3 | | -8(w+1)=48 | | (3x-3)-(10x-6)=3 | | x+3/4-2x=x+1/2 | | 4(x−6)=3(5−3x) | | 14+9c=41 | | 5x+389=3461 | | 8=4(11+r) | | 3(4x+2-4x-2=-4 | | 68=20+8w | | 2x^2–3x+1=0 | | 8/3/5/7=14/5/x | | 14+t=21 | | 4x-1÷=x+7 | | 15=-y/5+16 | | 5p-10=-65 | | 24/3=96/x | | 6+u=15 | | x/4+2/3=x/6 | | 3y-8=10y+13 | | 5-3x+6-2x+5x=2x-12x+5+10 | | −3+c2−2c=0 | | 2a^2-7a=-5 | | 5(p+4)=3p–3 | | 10x–3(2x–15)=7x |